Services Trade in Developing Asia: A Case Study of the Banking and Insurance Sector in Bangladesh - Salahuddin Ahmad; Dilli Raj Khanal (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
This study assesses the strengths and weaknesses of reforms in the banking and insurance industries. Banking sector performance is analysed using various indicators as well as Principle Component Analysis techniques. A comparative case study of three banks with different ownership structures is presented. The study concludes with important conclusions and policy implications for future reforms based on the findings.
Keywords: F1; 330; Service Trade; Bangladesh